Multi-environment analysis of nutritional and grain quality traits in relation to grain yield under drought and terminal heat stress in bread wheat and durum wheat - Kakanur Jagadeesha, Yashavanthakumar; Navathe, Sudhir; Krishnappa, Gopalareddy; Ambati, Divya; Baviskar, Vijendra; Biradar, Suma; Magar, Nilesh; Mishra, Chandra Nath; Mamrutha, Harohalli Masthigowda; Govindan, Velu; Singh, Gyanendra Pratap; Singh, Gyanendra (Wiley, 2024)
Heat and drought are two important constraints to global wheat productivity; understanding the genotypic responses for quality parameters under harsh production conditions (drought and heat) is very important for developing nutrient-dense wheat varieties. A set of 15 modern bread wheat (Triticum aestivum L. subsp. aestivum) and durum wheat (Triticum turgidum subsp. durum) cultivars were tested in nine environments, including three different production conditions (normal, heat and drought) during 2020-21. Genotype stability performance for yield, nutrition and quality parameters is assessed using multienvironment trials through AMMI and GGE Biplot analysis. We discovered intriguing stress dynamics in grain zinc content (Zn) and grain iron content (Fe). Under heat stress, zinc concentration increases but decreases under drought stress, while iron does the opposite. Selecting zinc, starch and kernel weight under terminal heat stress can boost yield. Protein content and yield are inversely related, making it difficult for breeders to optimise both traits. G x E interactions and stability indices across all environments have found genotypes with high-yielding stable genotypes, G12 (MP1358) (42.09 ppm) and G5 (HI1544) (42.41 ppm) have high Fe content. G12 (MP1358) (14.98%) ranked highest in protein concentration. Meanwhile, for Zn content, G11 (MACS 4058) (45.23 ppm) and G15 (WH730) (42.44 ppm) were top performers across environments. G7 (HI 1636) and G12 (MP1358) stand out as a win-win genotype for their high potential and stability in yield, protein, Zn and Fe content. Our study shows the complex relationships and possible suggestions for targeted breeding programmes under heat and drought stress conditions to improve wheat grain quality and micronutrient profiles without yield loss.